A study of factors affecting consumer purchase intention towards halal labelled cosmetics and personal care products in Malaysia - Phuah, Kit Teng; Wan Jusoh, Wan Jamaliah (worldconferences.net, 2018)
Halal labelled cosmetic and personal care products industries can be more effective to position Halal values to new insights for championing to drive the Halal economy in Malaysia. The persistence of this paper is to identify the consumers’ purchase intention for Halal labelled cosmetic and personal care product. A survey was conducted in Malaysia where 573 respondents were interviewed by self administration questionnaires. The modified Theory of Reasoned Action (TRA) was applied in this study. Descriptive analysis, factor analysis and binary regressions were used to accomplish the objective. Six factors which will influence the consumer behavioural intention were determined in this study which was past and current experience of using the product, religiosity, Halal logo and certification, subjective norm, attitude and knowledge. However, the result of binary logistic regression indicate that only consumer knowledge, past and current experience, subjective norm and religiosity will influence the consumers’ intention to purchase Halal labelled cosmetic and personal care product.